Kaji eksperimental pengaruh variasi impeller terhadap kinerja pump as turbine - Asral (Prosiding SNTTM, 2025)
The increasing demand for electrical energy has driven the utilization of renewable energy sources, one of which is water energy. Centrifugal pumps operated in reverse as Pump as Turbine (PAT) are a simple and economical solution for small-scale power plants. This study analyzes the effect of impeller shape variations open, half closed, and fully closed on PAT performance through experimental testing with valve opening variations (50–100%) and electrical loads (30-300 watts). The parameters observed include flow rate, rotational speed, and hydraulic efficiency. The results show that the open impeller produces the largest flow rate (63.369 m³/h), the semi closed impeller has the highest rotational speed (1958 rpm), while the fully closed impeller provides the highest efficiency (58%). The impeller shape has been proven to have a significant effect on PAT performance, particularly in increasing energy conversion efficiency. This research contributes to the selection of optimal impeller designs for small-scale hydroelectric power generation systems and the development of more efficient renewable energy technologies